Pengaruh Celebrity Endorsement Terhadap Minat Beli Melalui Brand Image (Studi Pada Mahasiswa Kota Tegal) - Eko Prasojo (Journal Competency of Business, 2019)
Famous celebrities are a huge consideration for being a communicator in an advertisement, commonly referred to as endorser celebrity. Celebrities who are on the rise or popular are believed to be more able to influence someone to take certain actions in accordance with the initial purpose. Advertising is one of the strategies undertaken by companies to communicate products and introduce a brand. This form of communication can be done in a variety of ways, one of which is the advertisement used by Luwak White Koffie's products, in which the ad uses Celebrity Endorsement which aims to attract the attention of potential consumers when they see it. Celebrity Endorsement can have an impact on the world of advertising, depending on the personality and popularity of the celebrity. The purpose of this study is to determine the credibility of Celebrity Endorsement on Brand Image, to know the Celebrity Endorsement Expertise on Brand Image, to determine the Attractiveness of Celebrity Endorsement towards Brand Image, to find out the trustworthiness of Celebrity Endorsement towards Brand Image, to determine the Celebrity Endorsement power Brand Image and to find out the Brand Image of Buying Interest. The results showed that there was a positive and significant influence between credibility, expertise, attractiveness, trust, power (strength) on brand image of Luwak White Koffie consumers and there was a positive and significant effect between brand image on consumer buying interest of Luwak White Koffie products in the City Tegal.